2004
DOI: 10.1124/jpet.103.049718
|View full text |Cite
|
Sign up to set email alerts
|

Brain Stimulation for Neurological and Psychiatric Disorders, Current Status and Future Direction

Abstract: Interest in brain stimulation therapies has been rejuvenated over the last decade and brain stimulation therapy has become an alternative treatment for many neurological and psychiatric disorders, including Parkinson's disease (PD), dystonia, pain, epilepsy, depression, and schizophrenia. The effects of brain stimulation on PD are well described, and this treatment has been widely used for such conditions worldwide. Treatments for other conditions are still in experimental stages and large-scale, well controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 68 publications
0
14
0
1
Order By: Relevance
“…Based on this observation, chronic vagus nerve stimulation (VNS) with an implanted electrode and stimulator (for review see Schachter and Schmidt, 2004) is employed for intractable epilepsy. Independently, another stimulation therapy, deep brain stimulation (DBS), is also used clinically for treating epilepsy (Chang, 2004;Theodore and Fisher, 2004). With the underlying mechanisms remaining unknown, these two methods have been studied separately.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Based on this observation, chronic vagus nerve stimulation (VNS) with an implanted electrode and stimulator (for review see Schachter and Schmidt, 2004) is employed for intractable epilepsy. Independently, another stimulation therapy, deep brain stimulation (DBS), is also used clinically for treating epilepsy (Chang, 2004;Theodore and Fisher, 2004). With the underlying mechanisms remaining unknown, these two methods have been studied separately.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…It has been suggested that STN-DBS affects neuronal membrane potentials and voltage-dependent calcium channels surrounding the pathologic circuitry [ 9 ] . In doing so, DBS may be altering the fi ring pattern of STN neurons to immediately produce a therapeutic effect at the electrode's tip [ 42,43 ] . It is also possible that the stimulation is not affecting the cell bodies; rather, the axons carrying signals into the STN from other areas may be the target of the stimulation's effects [ 9 ] .…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…More recently, DBS has been used to treat endogenous depression [ 42 ] . Like PD, major depressive disorder (MDD) was initially treated using ablative surgeries until monoamine oxidase inhibitors and tricyclic antidepressants were found to effectively improve depressive symptoms [ 125 ] .…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…The latter procedure is not limited to PD, and is also used to treat disorders such as dystonia, pain, depression, and obsessive compulsive disorders [11]. Intriguingly, both electrical stimulation and the lesion of motor targets in the basal ganglia appear to reverse movement abnormalities such as tremor, without any obvious deleterious effects on other aspects of movements [12].…”
Section: Introductionmentioning
confidence: 98%